Predictors of psychological distress among divorced women in Iran - Esmaeili, Nooshin Sabour; Yaacob, Siti Nor; Juhari, Rumaya; Schoebi, Dominik (Taylor & Francis, 2015)
Previous research has consistently found that divorce is associated with psychological distress. This study expands existing research by considering age, education, employment, income, length of divorce, number of children, and economic hardship as predictors of postdivorce psychological distress among divorced women in Iran. This study examines 800 divorced women in Iran 30 to 48 years old who had been divorced for no more than 2 years. Results demonstrated that education, number of children, and economic hardship together predict 63.6% of the variance in psychological distress among divorced women. Economic hardship was found to be the strongest contributor. Recommendations for researchers and implications for clinicians are discussed.